Reducing waiting and turnaround time in Round Robin scheduling algorithm - اسماعيل, علي (Latakia University Journal -Engineering Sciences Series, 2023)
The operating system is an intermediary between the user and the computer hardware. It provides an interface that hides from the user the complexity of dealing with hardware, and allocates the resources represented by the processor and main memory to processes in a way that improves the performance of the system. To execute any program, it must be moved to main memory so that it becomes a process ready to be executed on the processor. In a multitasking operating system, it is allowed to run multiple jobs simultaneously. The ready processes for execution are stored in a special queue called the ready queue, where the scheduler chooses the next process to be executed. The scheduler selects process based on the scheduling algorithms. These algorithms aim to arrange the execution of processes in an optimal manner, as there are several criteria for optimizing the performance of scheduling algorithms, namely: improving CPU Utilization, reducing waiting time, reducing turnaround time, in addition to reducing the number of context switch times. This paper provides an improvement on the performance of the round Robin scheduling algorithm, which is one of the most important scheduling algorithms. It reduces waiting time and turnaround time by suggesting a dynamic quantum rather than using a fixed quantum. The time allotted for each process is calculated by calculating the median value of the burst time values for all the processes within the ready queue. The proposed algorithm is compared with a group of other scheduling algorithms in terms of turnaround time, waiting time and number of context switches. The results show the superiority of the proposed algorithm over the other round Robin scheduling algorithms